Tunable Crossed Andreev Reflection and Elastic Cotunneling in Hybrid Nanowires - Alberto Bordin; Guanzhong Wang; Chun-Xiao Liu; Sebastiaan L. D. ten Haaf; Nick van Loo; Grzegorz P. Mazur; Di Xu; David van Driel; Francesco Zatelli; Sasa Gazibegovic; Ghada Badawy; Erik P. A. M. Bakkers; et al. (Physical Review X, 2023)
A short superconducting segment can couple attached quantum dots via elastic cotunneling (ECT) and crossed Andreev reflection (CAR). Such coupled quantum dots can host Majorana bound states provided that the ratio between CAR and ECT can be controlled. Metallic superconductors have so far been shown to mediate such tunneling phenomena, albeit with limited tunability. Here, we show that Andreev bound states formed in semiconductor-superconductor heterostructures can mediate CAR and ECT over mesoscopic length scales. Andreev bound states possess both an electron and a hole component, giving rise to an intricate interference phenomenon that allows us to tune the ratio between CAR and ECT deterministically. We further show that the combination of intrinsic spin-orbit coupling in InSb nanowires and an applied magnetic field provides another efficient knob to tune the ratio between ECT and CAR and optimize the amount of coupling between neighboring quantum dots.